Duration of Hospital Stay in Alcohol/Substance Addictions and Psychiatric Disorders: A 12-Year Retrospective Analysis - Bahadir Geniş; Behcet Cosar (Baqiyatallah University of Medical Sciences, 2020)
Background: Mental disorders are generally a significant reason for increased morbidity. They constitute a serious disease burden. One of the main reasons for this disease burden is long hospitalization periods. Objective: The current study investigated the length of hospital stay and the variables affecting it in patients treated in the Gazi University Hospital Psychiatry Department between 2005-2016. Methods: Patient diagnoses were analyzed according to the International Classification of Diseases 10th Revision (ICD-10). Data was obtained for 7027 hospitalizations over a 12-year period. Records of repeated hospitalizations, non-psychiatric primary diagnoses, and missing data were not included in the analysis. As a result, data from 5129 hospitalizations were included in the analysis. Results: Mean age of the sample was 45.27±14.69, and 62.5% (n=3204) of the patients were male. Mean hospitalization period was 28.66±17.25 days. Schizophrenia and depressive disorder significantly prolonged hospital stay, while substance addiction shortened the duration of hospitalization (P < 0.001). It was found that the duration of hospitalization decreased significantly over the years (P < 0.001). Advanced age (P < 0.001), recurrent admission (P < 0.001), and female gender (P = 0.029) were other variables affecting this period. Conclusion: Schizophrenia and depression are the most common psychiatric disorders in the inpatient service, and these disorders prolong hospitalization periods. The duration of hospital stay is considerably less in substance addiction than in other psychiatric disorders. Non-clinical variables, such as year of hospitalization, may affect the length of hospital stay.